Family Caregivers’ Coping Strategies in Taking care for Relatives with Schizophrenia: A Phenomenological Study - Indra Gunawan; Nia Restiana; Rosy Rosnawanty; Saryomo Saryomo (Program Studi Keperawatan Universitas Muhammadiyah Tasikmalaya, 2023)
Schizophrenia is a complex mental health disorder that requires long-term treatment even throughout the patient's life cycle. Nowadays, caring for patients with schizophrenia has been shifted from hospital-based to community, and it requires the family as the caregivers. The study's objective was to explore caregivers' coping strategies experiences in taking care of someone with schizophrenia in their family. This study uses a phenomenological qualitative approach to explore caregiver experiences. The sampling technique uses purposive sampling by selecting caregivers who are close relatives of the client, have lived with their ill relatives for at least one year, and bear most of the care responsibilities. Data were collected using an online interview following semi-structured questions as a reference. Then the data collected was analyzed by grouping each critical statement. In the end, the essential meanings are used as the core theme. The researcher achieved data saturation after interviewing eight caregivers. This study found two types of coping strategies used by caregivers: problem-focused coping strategies and emotional-focused coping strategies. In conclusion, caregivers use various techniques to solve problems faced due to caregiving. Moreover, caregivers feel a combination of one or two types of strategy is effective as their strategic coping.